Pengaruh Penggunaan Media Pembelajaran Berbasis Phet Terhadap Minat dan Hasil Belajar IPA Siswa SMPN 6 Kota Bima - Lasmijiani, Lasmijiani; Rahmawati, Eka; Subhan, Muhammad (Universitas Nggusuwaru, 2024)
This research aims to measure the effect of using PhET-based learning media on the interest and learning outcomes of physics students at SMPN 6 Kota Bima. The research method used was a quasi-experiment with a nonequivalent control group design. This research involved two groups, namely the experimental class which used PhET media and the control class which used conventional methods. The research results showed that the use of PhET media significantly increased students' interest in learning, with the average learning interest score for experimental class students reaching 71.29 (high category), compared to the control class of 47.79 (fairly high category). Apart from that, student learning outcomes also showed a significant increase with the average post-test score for the experimental class being 82, while the control class only reached 64. Based on the t-test results, there was a significant difference between the two groups with a calculated t value of 4.865 ( p < 0.05), which shows that PhET media is more effective in improving student learning outcomes compared to conventional methods (package books).